Choosing Wisely Canada – pediatric otolaryngology recommendations - Mitchell McDonough; Kalpesh Hathi; Gerard Corsten; Christopher J. Chin; Paolo Campisi; Jonathan Cavanagh; Neil Chadha; M. Elise Graham; Murad Husein; Liane B. Johnson; Jodi Jones; Bruce Korman; et al. (Journal of Otolaryngology - Head and Neck Surgery)
Abstract The Choosing Wisely Canada campaign raises awareness amongst physicians and patients regarding unnecessary or inappropriate tests and treatments. Using an online survey, members of the Pediatric Otolaryngology Subspecialty Group within the Canadian Society of Otolaryngology – Head & Neck Surgery developed a list of nine evidence based recommendations to help physicians and patients make treatment decisions regarding common pediatric otolaryngology presentations: (1) Don’t routinely order a plain film x-ray in the evaluation of nasal fractures; (2) Don’t order imaging to distinguish acute bacterial sinusitis from an upper respiratory infection; (3) Don’t place tympanostomy tubes in most children for a single episode of otitis media with effusion of less than 3 months duration; (4) Don’t routinely prescribe intranasal/systemic steroids, antihistamines or decongestants for children with uncomplicated otitis media with effusion; (5) Don’t prescribe oral antibiotics for children with uncomplicated tympanostomy tube otorrhea or uncomplicated acute otitis externa; (6) Don’t prescribe codeine for post-tonsillectomy/adenoidectomy pain relief in children; (7) Don’t administer perioperative antibiotics for elective tonsillectomy in children; (8) Don’t perform tonsillectomy for children with uncomplicated recurrent throat infections if there have been fewer than 7 episodes in the past year, 5 episodes in each of the past 2 years, or 3 episodes in each of the last 3 years; and (9) Don’t perform endoscopic sinus surgery for uncomplicated pediatric chronic rhinosinusitis prior to failure of maximal medical therapy and adenoidectomy.